Three-time renal recovery after dialysis-dependent acute kidney injury in a 75-year-old woman with hypertensive nephropathy: A case report with five-year follow-up - Ostapenko, Tetyana; Marchenko, Valeria; Holovanova, Alina; Dyvynskyy , Mark (Ukrainian Journal of Nephrology and Dialysis, 2025)
Dialysis-dependent acute kidney injury (AKI-D) in elderly patients with chronic comorbidities is typically associated with poor renal prognosis. Reports of repeated recovery after multiple AKI-D episodes are rare. In this case, we describe a 75-year-old woman with hypertensive nephropathy who experienced three distinct episodes of AKI-D over five years. The first episode occurred in 2021 in the setting of a hypertensive crisis with oliguria and severe azotemia, requiring eight sessions of hemodialysis. The second episode followed COVID-19 vaccination and excessive use of nonsteroidal anti-inflammatory drugs (NSAIDs), leading to 14 sessions of hemodiafiltration. The third episode developed in 2025 after a COVID-19 infection and concomitant antibiotic and NSAID therapy, again requiring temporary kidney replacement therapy. Remarkably, in each instance, the patient regained sufficient kidney function to discontinue hemodialysis, with recovery documented at serum creatinine levels of 97 µmol/L, 115.8 µmol/L, and a current value of 147.3 µmol/L, corresponding to an estimated glomerular filtration rate of 32 mL/min/1.73 m². At discharge after the first episode of AKI, the condition was assessed as CKD stage 5 (eGFR 13 mL/min/1.73m²), and an arteriovenous fistula was created, but kidney function fully normalized within the next two weeks. Vascular access was complicated by aneurysmal dilation of an arteriovenous fistula, necessitating surgical closure. This case highlights the potential for renal recovery even in elderly patients with comorbidities and raises important considerations regarding prognostic evaluation, nephrotoxic medications, and vascular access management.